Efficacy of a transdiagnostic guided internet-delivered intervention for emotional, trauma and stress-related disorders in Mexican population: study protocol for a randomized controlled trial - De la Rosa- Gómez, Anabel; Castellanos-Vargas, Rosa Olimpia; Esquivel Santoveña, Esteban Eugenio; Arenas-Landgrave, Paulina; Santillán-Torres, Carolina; García-Flores, Raquel; de la Rosa‑Gómez, Anabel; Flores‑Plata, Lorena A.; Domínguez‑Rodríguez, Alejandro; Berra‑Ruiz, Enrique; Silvestre‑Ramírez, Rocío; Miranda‑Díaz, Germán Alejandro; et al. (2022)
Background Emotional and stress-related disorders show high incidence, prevalence, morbidity, and comorbidity rates in Mexico. In recent decades, research findings indicate that cognitive behavioral interventions, from a disorder-specific perspective, are the effective front-line treatment for anxiety and depression care. However, these treatments are not often used. Reasons include limited access and low availability to effective interventions and comorbidity between mental disorders. Emotional deregulation of negative affectivity has been found to be a mediating factor in addressing emotional disorders from a transdiagnostic perspective, aimed at two or more specific disorders. In addition, technological advancement has created alternatives for psychological assistance, highlighting the possibilities offered by technologies since Internet-supported intervention programs have been empirically tested for effectiveness, efficiency and efficacy and can be key to ensuring access to those who are inaccessible. The aim of the study is to evaluate the efficacy, moderators of clinical change and acceptability of a transdiagnostic guided Internet-delivered intervention versus a transdiagnostic self-guided Internet-delivered intervention for emotional, trauma and stress-related disorders, and waiting list in community sample. Methods A three-armed, parallel group, superiority randomized controlled clinical trial with repeated measurements at four times: pretest, posttest, follow-up at 3, 6 and 12 months. Outcomes assessor, participant, care provider and investigator will be blinded. Participants aged 18 to 70 years will be randomly allocated 1:1:1 to one of three study arms: a) Transdiagnostic guided internet-delivered intervention with synchronous assistance, b) Transdiagnostic self-guided internet-delivered intervention, c) Waiting list group. Based on sample size estimation, a minimum of 207 participants (69 in each intervention group) will be included. Discussion The study could contribute to improving the efficacy of transdiagnostic internet-delivered interventions to promote the dissemination of evidence-based treatments and eventually, to decrease the high prevalence of emotional and trauma-related disorders in the Mexican population.